Development of Authentic Assessment-Based Performance Assessment Tools on Buffer Solution Material - Rina Novianty; Aryandi Sudika; Fitriani Fitriani; Mukhsin Mukhsin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study aims to develop and evaluate a performance assessment tool based on authentic assessment on buffer solution material in chemistry learning in secondary schools. The study uses a research and development (R&D) approach with reference to the 4-D model which includes the define, design, develop, and disseminate stages. The developed product includes an assessment specification table, a performance assessment grid, analytical rubrics in the cognitive, affective, and psychomotor domains, student performance tasks, student activity sheets, and a learning implementation plan. The validity of the tool was determined through expert judgment and analyzed using the content validity coefficient, while the practicality and effectiveness were tested through a limited trial on 40 grade XI science students. The results showed that all components of the performance assessment tool met the criteria of validity (V = 0.89–1.00), practicality (average value of implementation T = 4.35), and effectiveness. The effectiveness of the tool is demonstrated by an increase in cognitive learning outcomes from 47.5% to 80%, the achievement of affective and psychomotor learning outcomes, which are predominantly in the good and very good categories, and a positive student response of 89.79%. These findings indicate that the developed performance assessment tool is capable of supporting comprehensive and authentic chemistry learning assessments and has the potential to improve the quality of student learning processes and outcomes.